Balnnophora reflexa Beccari, A new record for Mahua, Crocker Range, Sabah Parks, Sabah Malaysia - Normally Muslim; Azniza Mahyudin; Liew, Thor Seng; Maklarin Larkin; Dunsul Sinail (Flora malaysiana Sdn Bhd, 2008)
The root parasitic plant Balanophora retlexa Beccari is reported for the first time from Mahua, Crocker Range, Sabah Parks, Sabah though it has been reported to be found around Mount Kinabalu, Kinabalu Park, Sabah. In Mahua, on Crocker Range at an elevation of 1050 m asl, the Balanophora reflexa was found on the roots of host plants covered with humus topsoil which in turn was covered with leaf litter in the shady part of the tropical forest. The male and female flowers grow from different clumps and are usually found to be not so close to each other. The flowers exude a smell similar to that of Pandanus amaryIlifulius, which can be a strong indicator of its presence in the area. In addition to the morphological description, we sequenced a fragment of internal transcribed spacers (ITS) of nuclear ribosomal DNA.